Do Taxes Matter for FDI Flows to Mexico? - Gonzalez del Real, Pablo (2010)
There have been several studies focusing on the factors influencing the location decision of multinationals. However, the empirical literature considering tax policies as a determinant of foreign direct investment (FDI) has been limited in several respects, with most studies focused on developed countries and exclusively considering host country taxes. The aim of this paper is to extend those boundaries by analyzing the effect of taxes on FDI flows to a developing country and incorporating both host and home country tax rates as determinants.